2016
DOI: 10.1016/j.jid.2015.12.042
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotyping of Stage III Melanoma Reveals Parameters Associated with Patient Prognosis

Abstract: Stage III metastatic melanomas require adequate adjuvant immunotherapy to prevent relapses. Prognostic factors are awaited to optimize the clinical management of these patients. The magnitude of metastatic lymph node invasion and the BRAFV600 activating mutation have clinical significance. Based on a comprehensive immunophenotyping of 252 parameters per patient in paired blood and metastatic lymph nodes performed in 39 metastatic melanomas, we found that blood markers were as contributive as tumor-infiltrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 34 publications
(40 reference statements)
4
41
0
1
Order By: Relevance
“…Tumor infiltrated leukocytes (TILs) were isolated from metastatic lesions of melanoma patients as previously described. 61 Briefly, tumor samples were minced and then digested using a mix of Collagenase IV (50 IU/mL), hyaluronidase (280 IU/mL) and Dnase1 (30 IU/mL) (all from Sigma-Aldrich) in RPMI1640 + 1% penicillin/streptomycin (Gibco Inviotrogen). Samples were subjected to gentleMACS dissociation (Miltenyi Biotech).…”
Section: Microarray Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor infiltrated leukocytes (TILs) were isolated from metastatic lesions of melanoma patients as previously described. 61 Briefly, tumor samples were minced and then digested using a mix of Collagenase IV (50 IU/mL), hyaluronidase (280 IU/mL) and Dnase1 (30 IU/mL) (all from Sigma-Aldrich) in RPMI1640 + 1% penicillin/streptomycin (Gibco Inviotrogen). Samples were subjected to gentleMACS dissociation (Miltenyi Biotech).…”
Section: Microarray Analysismentioning
confidence: 99%
“…Digested samples were washed in PBS and passed through a 70 μm cell strainer before to be counted and stored in liquid nitrogen using CryoMaxx medium (PAA Laboratories). 61 PBMCs and TILs were quickly thawed in culture media (RPMI1640 [Gibco, Invitrogen] + 10% human AB + serum [Institut de Biotechnologies Jacques Boy] + 2 mM L-Glutamine + 1% sodium/pyruvate + 1% penicillin/streptomycin [all from Gibco, Invitrogen]), washed, counted and seeded at 0.3 × 10 6 /mL per well in 48 well-plate in culture medium and incubated with or without Roferon® (1000 UI/mL, Roche Pharma) and LPS (10 ng/mL, Sigma). After 24-60 h of incubation, cells were harvested, washed, immediately resuspended in RLT + Buffer and stored at -80°C until RNA extraction and quantification.…”
Section: Microarray Analysismentioning
confidence: 99%
“…Also, regulatory Treg within tumor-infiltrating lymphocytes are indicative of dismal prognosis, specifically in BRAF mutated melanoma. High natural toxicity receptor NKG2D expression on CD8+ tumor-infiltrating lymphocytes, low level of Treg, and low PD-L1 expression on circulating T cells predicted prolonged overall survival in the multivariate Cox analysis model [138]. …”
Section: Tumor Microenvironment and Biomarkersmentioning
confidence: 99%
“…This is reinforced by the effectiveness of immunotherapies based on immune checkpoint blockers that allow for reversal of melanoma-induced immunosuppression correlated with the presence of neoantigens expressed by the tumor (McGranahan et al, 2016;Van Allen et al, 2015). Consistent with this hypothesis, some studies suggested that the presence, number, or quality of T lymphocyte infiltrates, specifically CD8 + T cells, is an independent and favorable prognostic factor in melanoma (Erdag et al, 2012;Jacquelot et al, 2016;de Moll et al, 2015;Piras et al, 2005). Ongoing investigations are analyzing the host immune response against cancer to evaluate the prognostic impact of in situ immune-cell infiltrates in tumors and defined as an "immunoscore" (Galon et al, 2012).…”
Section: Discussionmentioning
confidence: 92%